2015
DOI: 10.1007/s12291-014-0475-8
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Role of Peroxynitrite Induced DNA Damage in Human Diseases: A Special Focus on Poly(ADP-ribose) Polymerase (PARP)

Abstract: Peroxynitrite is formed in biological systems when nitric oxide and superoxide rapidly interact at near equimolar ratio. Peroxynitrite, though not a free radical by chemical nature, is a powerful oxidant which reacts with proteins, DNA and lipids. These reactions trigger a wide array of cellular responses ranging from subtle modulations of cell signaling to overwhelming oxidative injury, committing cells to necrosis or apoptosis. The present review outlines the various peroxynitrite-induced DNA modifications w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 229 publications
(277 reference statements)
2
32
0
1
Order By: Relevance
“…The treatment of smokeless tobacco extract induced higher concentrations of reactive oxygen species and malondialdehyde in cultured human oral mucosa fibroblasts cells (Li et al, 2018). Peroxynitrite, though not a free radical by chemical nature, is a powerful oxidant that reacts with proteins, DNA, lipids, oxidative injury, committing cells to necrosis or apoptosis (Islam et al, 2015). The levels of peroxynitrites are increased in plasma of chewing tobacco users.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of smokeless tobacco extract induced higher concentrations of reactive oxygen species and malondialdehyde in cultured human oral mucosa fibroblasts cells (Li et al, 2018). Peroxynitrite, though not a free radical by chemical nature, is a powerful oxidant that reacts with proteins, DNA, lipids, oxidative injury, committing cells to necrosis or apoptosis (Islam et al, 2015). The levels of peroxynitrites are increased in plasma of chewing tobacco users.…”
Section: Discussionmentioning
confidence: 99%
“…The latter process results in diminished NO bioavailability [8, 51] and also contributes to the over-activation of PARP-1 via oxidants induced damage of the DNA [12, 26, 47, 52]. Excess formation of poly(ADP-ribose) polymers (PAR) alters nuclear NAD + metabolism, originally considered as the main initiator of the caspase-independent form of cell death by cellular metabolic instability and a further boost in ROS production via mitochondrial dysfunction [13, 53, 54].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the NAD + preserving effects, it prevents nucleus-to-mitochondria death signaling [47] and also interferes with stress-related biases in intracellular signaling routes [55, 57]. Amongst these, activation of JNK is considered to be a key event in the process of parthanatos via mitochondria damaging properties resulting in AIF release [47, 52, 5860]. In our study, nuclear translocation of AIF was observed in control hypertensive animals (Fig 2C), indicating PARP-1 over activation initiated cell death events [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] PN has a toxic effect on the biological system by directly reactingw ith the sulfydryl groups at ar ate that is 10 3 times greater than hydrogen peroxide at pH 7.4 and affects cellular metabolism through lipid peroxidation. [8] In addition PN alters the function of mitochondria [9] and promotes DNA damage [10] due to its high reactivity.T he SOD enzyme also reacts with peroxynitrite due to the presence of Cu in its active site which results in the inhibition of enzymatic activity ands imultaneousg eneration of the toxic nitronium ion (NO 2 + ). [7] Changes in the protein structurei np resence of PN are often ar esult of oxidative modification of certain residues like methionine andc ysteine.…”
Section: Introductionmentioning
confidence: 99%